THE IMPORTANCE OF FILLER IN THE FORMATION OF THE STRUCTURE OF CONCRETE - Ruzmetov Fazliddin Sharifboevich; Amirov Temirbek Tursoat ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
. The physical and mechanical properties of concrete are influenced by the amount and character of the contact zone between the cement stone and the filler. According to the data obtained, the amount of the contact zone may differ significantly depending on the type of filler.